mathlib documentation

core.init.data.int.basic

inductive int  :
Type

@[instance]

@[instance]

Equations
def int.repr  :

Equations
@[instance]

Equations
theorem int.coe_nat_eq (n : ) :

def int.zero  :

Equations
def int.one  :

Equations
@[instance]

Equations
@[instance]

Equations
theorem int.of_nat_one  :

def int.sub_nat_nat  :

Equations
theorem int.sub_nat_nat_of_sub_eq_zero {m n : } :
n - m = 0int.sub_nat_nat m n = int.of_nat (m - n)

theorem int.sub_nat_nat_of_sub_eq_succ {m n k : } :
n - m = k.succint.sub_nat_nat m n = -[1+ k]

def int.neg  :

Equations
def int.mul  :

Equations
@[instance]

Equations
@[instance]

Equations
@[instance]

Equations
def int.sub  :

Equations
@[instance]

Equations
theorem int.neg_zero  :
-0 = 0

theorem int.of_nat_add (n m : ) :

theorem int.of_nat_mul (n m : ) :

@[simp]
theorem int.of_nat_eq_coe (n : ) :

theorem int.neg_succ_of_nat_coe (n : ) :
-[1+ n] = -(n + 1)

@[simp]
theorem int.coe_nat_add (m n : ) :
(m + n) = m + n

@[simp]
theorem int.coe_nat_mul (m n : ) :
m * n = (m) * n

@[simp]
theorem int.coe_nat_zero  :
0 = 0

@[simp]
theorem int.coe_nat_one  :
1 = 1

@[simp]
theorem int.coe_nat_succ (n : ) :
(n.succ) = n + 1

theorem int.coe_nat_add_out (m n : ) :
m + n = m + n

theorem int.coe_nat_mul_out (m n : ) :
(m) * n = m * n

theorem int.coe_nat_add_one_out (n : ) :
n + 1 = (n.succ)

theorem int.coe_nat_inj {m n : } :
m = nm = n

theorem int.coe_nat_eq_coe_nat_iff (m n : ) :
m = n m = n

theorem int.neg_succ_of_nat_inj_iff {m n : } :
-[1+ m] = -[1+ n] m = n

theorem int.neg_succ_of_nat_eq (n : ) :
-[1+ n] = -(n + 1)

theorem int.neg_neg (a : ) :
--a = a

theorem int.neg_inj {a b : } :
-a = -ba = b

theorem int.sub_eq_add_neg {a b : } :
a - b = a + -b

theorem int.sub_nat_nat_elim (m n : ) (P : → Prop) :
(∀ (i n : ), P (n + i) n (int.of_nat i))(∀ (i m : ), P m (m + i + 1) -[1+ i])P m n (int.sub_nat_nat m n)

theorem int.sub_nat_nat_add_right {m n : } :
int.sub_nat_nat m (m + n + 1) = -[1+ n]

theorem int.sub_nat_nat_add_add (m n k : ) :

theorem int.sub_nat_nat_of_ge {m n : } :
m nint.sub_nat_nat m n = int.of_nat (m - n)

theorem int.sub_nat_nat_of_lt {m n : } :
m < nint.sub_nat_nat m n = -[1+ (n - m).pred]

@[simp]
def int.nat_abs  :

Equations
@[simp]
theorem int.nat_abs_of_nat (n : ) :

theorem int.eq_zero_of_nat_abs_eq_zero {a : } :
a.nat_abs = 0a = 0

theorem int.nat_abs_pos_of_ne_zero {a : } :
a 0a.nat_abs > 0

@[simp]
theorem int.nat_abs_zero  :

@[simp]
theorem int.nat_abs_one  :

theorem int.nat_abs_mul_self {a : } :
(a.nat_abs) * a.nat_abs = a * a

@[simp]
theorem int.nat_abs_neg (a : ) :

theorem int.nat_abs_eq (a : ) :

theorem int.eq_coe_or_neg (a : ) :
∃ (n : ), a = n a = -n

def int.sign  :

Equations
@[simp]
theorem int.sign_zero  :
0.sign = 0

@[simp]
theorem int.sign_one  :
1.sign = 1

@[simp]
theorem int.sign_neg_one  :
(-1).sign = -1

def int.div  :

Equations
def int.mod  :

Equations
def int.fdiv  :

Equations
def int.fmod  :

Equations
def int.rem  :

Equations
@[instance]

Equations
@[instance]

Equations
def int.gcd  :

Equations
theorem int.add_comm (a b : ) :
a + b = b + a

theorem int.add_zero (a : ) :
a + 0 = a

theorem int.zero_add (a : ) :
0 + a = a

theorem int.sub_nat_nat_sub {m n : } (h : m n) (k : ) :

theorem int.add_assoc_aux1 (m n : ) (c : ) :

theorem int.add_assoc_aux2 (m n k : ) :

theorem int.add_assoc (a b c : ) :
a + b + c = a + (b + c)

theorem int.sub_nat_self (n : ) :

theorem int.add_left_neg (a : ) :
-a + a = 0

theorem int.add_right_neg (a : ) :
a + -a = 0

theorem int.mul_comm (a b : ) :
a * b = b * a

theorem int.mul_assoc (a b c : ) :
(a * b) * c = a * b * c

theorem int.mul_zero (a : ) :
a * 0 = 0

theorem int.zero_mul (a : ) :
0 * a = 0

theorem int.distrib_left (a b c : ) :
a * (b + c) = a * b + a * c

theorem int.distrib_right (a b c : ) :
(a + b) * c = a * c + b * c

theorem int.zero_ne_one  :
0 1

theorem int.of_nat_sub {n m : } :
m nint.of_nat (n - m) = int.of_nat n - int.of_nat m

theorem int.add_left_comm (a b c : ) :
a + (b + c) = b + (a + c)

theorem int.add_left_cancel {a b c : } :
a + b = a + cb = c

theorem int.neg_add {a b : } :
-(a + b) = -a + -b

theorem int.neg_succ_of_nat_coe' (n : ) :
-[1+ n] = -n - 1

theorem int.coe_nat_sub {n m : } :
n m(m - n) = m - n

def int.to_nat  :

Equations
theorem int.to_nat_sub (m n : ) :
(m - n).to_nat = m - n

def int.nat_mod  :

Equations
theorem int.one_mul (a : ) :
1 * a = a

theorem int.mul_one (a : ) :
a * 1 = a

theorem int.neg_eq_neg_one_mul (a : ) :
-a = (-1) * a

theorem int.sign_mul_nat_abs (a : ) :
(a.sign) * (a.nat_abs) = a